2021
DOI: 10.1016/j.xfre.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in access to fertility care: who’s in and who’s out

Abstract: Objective: To study the racial and socioeconomic characteristics of women seeking fertility care in a state with mandated insurance coverage for fertility testing and treatment. Design: Cross-sectional, self-administered survey. Setting: Academic fertility center in Illinois. Patient(s): Of 5,000 consecutive fertility care patients, 1,460 completed the survey and were included in the study sample. Intervention(s): None. Main Outcome Measure(s): Details about demographic characteristics and health care access o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…A survey from one such “mandated state,” Massachusetts, found that the majority of individuals accessing infertility services were Caucasian, highly educated, and wealthy [ 7 ]. The authors of the study identified “glaring disparities” and speculated that the reasons for these were “unclear and likely multifactorial.” Galic et al reported very similar findings in Illinois, another “mandated state” [ 8 ]. In their cross-sectional survey of 1460 fertility care patients, three quarters were White, and the vast majority (81.5%) reported an annual household income of >$100,000.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…A survey from one such “mandated state,” Massachusetts, found that the majority of individuals accessing infertility services were Caucasian, highly educated, and wealthy [ 7 ]. The authors of the study identified “glaring disparities” and speculated that the reasons for these were “unclear and likely multifactorial.” Galic et al reported very similar findings in Illinois, another “mandated state” [ 8 ]. In their cross-sectional survey of 1460 fertility care patients, three quarters were White, and the vast majority (81.5%) reported an annual household income of >$100,000.…”
mentioning
confidence: 70%
“…The authors of the study identified "glaring disparities" and speculated that the reasons for these were "unclear and likely multifactorial." Galic et al reported very similar findings in Illinois, another "mandated state" [8]. In their cross-sectional survey of 1460 fertility care patients, three quarters were White, and the vast majority (81.5%) reported an annual household income of >$100,000.…”
mentioning
confidence: 75%
“…This limits the generalizability of our findings but provides an opportunity for future evaluation of identified trends in more racially diverse groups. A need for expanded representation of diverse racial groups is especially important as racial and ethnic disparities in accessing fertility treatment have also been recorded with non-Hispanic white women being more likely to access care than Black and Hispanic counterparts [ 28 , 32 , 33 , 45 ]. Additionally, although the cohort aimed to develop a population-based sample of primary infertility, it could not capture women with primary infertility who did not seek medical evaluation or treatment for this condition.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a cross-sectional survey of 1460 women seeking fertility care at an academic center in Illinois, a state with mandated insurance coverage for fertility testing and treatment, assessed racial and socioeconomic characteristics and access to care [ 9 ]. Hispanic women in this population traveled twice as far as White and Black women.…”
Section: Main Textmentioning
confidence: 99%
“…Hispanic women in this population traveled twice as far as White and Black women. Additionally, Hispanic and Black women were twice as likely to report their income level and weight as barriers to treatment compared to White and Asian women [ 9 ]. Hispanic patients were significantly more likely than White patients to report being very/extremely worried about side effects of treatment, miscarriage, ectopic pregnancy and birth defects [ 10 ].…”
Section: Main Textmentioning
confidence: 99%